CAUSAL FACTORS OF THE INCREASE OF RELIGIOUS CONTESTATION IN BUMI DALUNG PERMAI HOUSING COMPLEX - Ayu Nerawati, Ni Gusti Agung (E-Journal of Cultural Studies; Vol 16 No 2 (2023): Volume 16 Number 2 May 2023DO - 10.24843/cs.2023.v16.i02.p04, 2023)
The strengthening of diversity contestation in Bumi Dalung Permai Housing is caused by several factors, namely, first, the factor of regional origins and the original cultural transition of the inhabitants, in this case that the origins to the area brought by the Bumi Dalung Permai Housing community are still firmly attached as an identity. The identity, both in terms of the language and culture of the community. In addition, there is a cultural shift that was originally intact to be adapted to the surrounding conditions due to the influence of resources. Second, the ideological and political factors adopted. In this factor every community has a different ideology even though it comes from the same area. Likewise with the politics adopted, every society has different political choices according to the ideology they believe in and a feeling of panic towards one political party or vice versa. Third, Socio-Economic Factors, explaining how these factors greatly affect the Bumi Dalung Permai Residential community. As it is known that money and social status control the social life of all groups. Fourth, the Globalization Factor that affects various fields in which its positive and negative sides cannot be denied. Globalization is characterized by ethnoscape , mediascape, technoskip , financescape and every element of globalization affects the Bumi Dalung Permai Housing environment from various sides. Keywords: globalization, religious contest, housing